Crystallization of bothrombin, a fibrinogen-converting serine protease isolated from the venom of Bothrops jararaca - Watanabe, L.; Vieira, D. F.; Bortoleto, R. K.; Arni, R. K. (Blackwell Munksgaard, 2002)
Bothrombin, a snake-venom serine protease, specifically cleaves fibrinogen, releasing fibrinopeptide A to form non-crosslinked soft clots, aggregates platelets in the presence of exogeneous fibrinogen and activates blood coagulation factor VIII. Bothrombin shares high sequence homology with other snake-venom proteases such as batroxobin (94% identity), but only 30 and 34% identity with human alpha-thrombin and trypsin, respectively. Single crystals of bothrombin have been obtained and X-ray diffraction data have been collected at the Laboratorio Nacional de Luz Sincrotron to a resolution of 2.8 Angstrom. The crystals belong to the space group P2(1)2(1)2(1), with unit-cell parameters a = 94.81, b = 115.68, c = 155.97 Angstrom.